Analysis of the Implementation of Mudharabah and Musharakah Financing Based on Profit Sharing - Nurhasanah, Siti; Qadariyah, Lailatul (Journal of Business and Economics Research (JBE), 2024)
This study examines the practice of mudharabah and musharakah financing at BMT Makin Amin, an Islamic savings and loan and financing cooperative in Kamal District, Bangkalan. Mudharabah financing is a partnership between a fund provider and a business manager, while musharakah financing involves a partnership between two parties who both provide funds and manage the business. Both types of financing operate on the principle of profit sharing, where profits and losses are shared based on an agreed ratio. The objectives of this study are to Analyze how general journal transactions reflect the principle of profit sharing and its effect on financial performance, Assess the impact of profit-sharing-based financing on the development of UMKM and the economic welfare of the community, and Provide recommendations to improve transparency and accountability in Islamic financing. The methodology used is descriptive qualitative research, with data collection through observation, in-depth interviews with BMT management, and documentation. The data analyzed includes primary and secondary data. The results showed that KSPPS BMT Makin Amin successfully implemented mudharabah and musyarakah financing in accordance with sharia principles, which contributed significantly to operating income and showed fluctuations during the research period.